Application of appropriate technology for banana cultivation in Sentang Village, Serdang Bedagai Regency - Lisdayani (Talenta Publisher Universitas Sumatera Utara, 2025)
Sentang Village has a tropical climate with low rainfall, and its geographical location is directly adjacent to the sea, so it is prone to salinity and drought stress. The Bina Mangrove Forest farmer group is cultivating yellow kepok bananas intensively on 15 ha of forest land in Sentang village. This farmer group has problems in the production and management aspects of their banana cultivation, namely low crop yields and soil organic matter, prone proneness to salinity and drought stress, high attacks by plant pests and no source of quality seeds. Based on the above problems, the Kosabangsa UNIVA-UMA 2024 team provided a solution, namely the implementation of the Appropriate Technology Package for Banana Cultivation in Sentang Village, consisting of Appropriate Technology Package 1. Kosabangsa Compost Formulation, 2. Banana Plant Care, 3. Improving the Quality of Banana Seeds. The implementation of package 1 were making local microorganisms from banana tubers and stems and compost from banana stems and brassica waste, for package 2 were pumping technology for water supply and ecological engineering with refugia, for package 3 were planting tissue culture banana seeds with a double row planting system for mulyo and barangan varieties. The evaluation test showed that farmers' knowledge increased by 75.5% from the pre-test results and the quality of knowledge and human resource skills was 100% achieved. The kosabangsa products namely “MOL BONGGOL PISANG, MOL GEDHEBOG PISANG, KOMPOS KOSABANGSA